Chiral pharmaceuticals: Environment sources, potential human health impacts, remediation technologies and future perspective. (December 2018) - Zhou, Yaoyu; Wu, Shikang; Zhou, Hao; Huang, Hongli; Zhao, Jia; Deng, Yaocheng; Wang, Hua; Yang, Yuan; Yang, Jian; Luo, Lin
Abstract: Chiral pharmaceuticals (CPs), including non-steroid anti-inflammatory drugs (NSAIDs), β-blockers and some herbicide and pesticides, are widely used in aquaculture, clinical treatment and many other fields. However, people are increasingly concerned about such ubiquitous pollutants, which can frequently be detected in contaminated soil and water. In large part, the significant sources of chiral pharmaceuticals stem from industrial processes, such as the direct discharge of untreated or incompletely treated wastewaters containing chiral pharmaceuticals, incorrect storage and use, animal wastes and biosolids. The main ways for human exposure to chiral pharmaceuticals are the disease treatment process and chiral pharmaceuticals contaminants. According to the results of a series of toxic studies, some diseases, even cancers, may be associated with exposure to certain chiral pharmaceuticals. Therefore, the treatment of chiral pharmaceuticals has become an important issue. The current advanced remediation techniques for chiral pharmaceuticals include the conventional method (sorption and sonolysis), biotransformation (an aerobic granular sludge-sequencing batch reactor and constructed wetland system) and advanced oxidation processes (ozonation and photocatalysis). Herein, in this review, we summarize the current status and sources of chiral pharmaceuticals, potential effects on human health, as well as the superiority, disadvantages and prospects of current advanced remediation technologies. Moreover, we also anticipate the prospect of the future research needed for chiral pharmaceuticals pollutant remediation. Highlights: Chiral pharmaceuticals in environment emerged as a serious threat. Chiral pharmaceuticals bring serious health effects to people and animals. A variety of remediation methods to treat chiral pharmaceuticals are summarized. Prospects for future research on chiral pharmaceuticals are presented.